Determination of Legacy and Emerging Perfluoroalkyl Substances (PFAS) in Biological Media using Liquid Chromatography–Tandem Mass Spectrometry - Fuentes, Valeria (East Carolina University, 2022)
Perfluoroalkyl acids (PFAS) are synthetic monomers used in a variety of manufacturing processes that have been shown to cause numerous adverse health outcomes. Newer PFAS compounds have been produced to curb their toxicity with questionable effectiveness. These compounds have been disposed of in wastewater and have polluted natural water systems. These compounds bioaccumulate in organisms, impact ecosystem health, and are consumed by humans. Therefore, it is important to determine the concentrations of these compounds in biological tissues to assess exposure and health ramifications. This is typically performed using liquid chromatography – mass spectrometry (LC-MS) as it is ubiquitous and sensitive. However, challenges associated with determining PFAS in complex biological matrices using MS arise from their structural properties, which results in limited ionization and fragmentation that impact sensitivity and selectivity, respectively. Liquid chromatography tandem mass spectrometry (LC-MS/MS) methods were developed to determine the concentrations of select perfluoro acids in biological media to ascertain how the exposure to these compounds results in observable health outcomes. First, LC and MS/MS parameters were separately optimized employing first generation PFAS standard compounds perfluorooctanoic acid (PFOA) and perfluoro octane sulfonic acid (PFOS). Using this background, we then expanded our protocols to monitor newer iterations of these compounds termed perfluoroether acids (PFEAs). PFEA compounds monitored in this study were 7H-Perfluoro-4-methyl-3,6-dioxaoctanesulfonic acid (Nafion byproduct 2) and 2,2- difluoro-2-(trifluoromethoxy)acetic acid, or perfluoromethoxyacetic acid (PFMOAA). The concentrations of these PFAS and PFEA compounds were determined in both mouse serum and urine. While significant research exists detailing the presence and toxicity of older generation PFAS, the toxicity of the two PFEA compounds and their concentrations in biological media has not been widely reported. Overall, we determine that our LC-MS/MS protocols can be used to rapidly and accurately detect the mg kg-1 concentrations of these select PFAS and PFEA compounds in mice, which can be correlated to previous reports and linked to observable negative health outcomes.
Keywords: Perfluoroalkyl acids; PFAS; concentration; biological tissues; biological matrices; Liquid chromatography tandem mass spectrometry; LC-MS/MS; biological media; exposure; perfluorooctanoic acid; PFOA; perfluoro octane sulfonic acid; PFOS; perfluoroether acids; PFEA; 7H-Perfluoro-4-methyl-3,6-dioxaoctanesulfonic acid; Nafion byproduct 2; 2,2- difluoro-2-(trifluoromethoxy)acetic acid; perfluoromethoxyacetic acid; PFMOAA; mouse serum; mouse urine; Perfluorinated chemicals--Health aspects; Perfluorinated chemicals--Toxicology; Tandem mass spectrometry